Integrative physiological study of adaptations induced by aerobic physical training in hypertensive hearts - Vieira, Suenimeire; Aguilar, Bruno A.; Veiga, Ana Catarine; Philbois, Stella V.; Freitas, Ana Caroline S.; Rodrigues, Karine P.; Tank, Jens; Souza, Hugo C. D. (Frontiers in Physiology, 2022)
Aerobic physical training reduces arterial pressure in patients with hypertension owing to integrative systemic adaptations. One of the key factors is the decrease in cardiac sympathetic influence. Thus, we hypothesized that among other causes, cardiac sympathetic influence reduction might be associated with intrinsic cardiac adaptations that provide greater efficiency. Therefore, 14 spontaneously hypertensive rats (SHR group) and 14 normotensive Wistar Kyoto rats (WKY group) were used in this study. Half of the rats in each group were trained to swim for 12 weeks. All animals underwent the following experimental protocols: double blockade of cardiac autonomic receptors with atropine and propranolol; echocardiography; and analysis of coronary bed reactivity and left ventricle contractility using the Langendorff technique. The untrained SHR group had a higher sympathetic tone, cardiac hypertrophy, and reduced ejection fraction compared with the untrained WKY group. In addition, reduced coronary bed reactivity due to increased flow, and less ventricular contractile response to dobutamine and salbutamol administration were observed. The trained SHR group showed fewer differences in echocardiographic parameters as the untrained SHR group. However, the trained SHR group showed a reduction in the cardiac sympathetic influence, greater coronary bed reactivity, and increased left intraventricular pressure. In conclusion, aerobic physical training seems to reduce cardiac sympathetic influence and increase contractile strength in SHR rats, besides the minimal effects on cardiac morphology. This reduction suggests intrinsic cardiac adaptations resulting in beneficial adjustments of coronary bed reactivity associated with greater left ventricular contraction.